KEADILAN EKONOMI DALAM PENDISTRIBUSIAN ZAKAT OLEH BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN TANAH DATAR - Hebby Rahmatul Utamy (IAIN Batusangkar, 2015)
This research was aimed at finding out the strategy and the process of distribution zakat by BAZNAS Tanah Datar to reach the economic justice. This research was qualitative case study by using interview and documentation as instruments. The results showed that the distribution of zakat by BAZNAS Tanah Datar was appropriate with the rules arranged by nash and Indonesia positive law. The process of collecting zakat was done before the process of distribution. The zakat was collected from all UPZ and sub-UPZ under BAZNAS from all private institutions. The distribution of zakat was arranged based on the amount of zakat from each UPZ. The process was followed by determination of quota based on productive mustahiq. The fact showed that every sub district has different potency to distribute zakat even though they are in the same regency, but all of the sub districts are under BAZNAS.Keywords: Economic Justice, Distributing Zakat, BAZNAS, Tanah Datar Regency